Implementation of Situational Leadership Model in Improving Company Performance - Pitri, Laila; Rozi, Fakhrur; Naqiya, Alfina Zsazsa (Journal of Business Administration and Strategy, 2025)
This research aimed to examine how the implementation of situational leadership models can improve work effectiveness in organizations. This research uses a descriptive qualitative approach with a library research method, which relies on various reference sources such as scientific journals, academic books, and previous research articles. The focus of the analysis is directed at understanding the leadership style applied by leaders in responding to the dynamics of employee readiness, as well as its impact on achieving organizational goals. The results showed that leaders who are able to adjust their leadership style according to the readiness level of their subordinates tend to be more successful in building productive work teams, increasing motivation, and creating a supportive work environment. The situational leadership model is also proven to be able to increase loyalty and collaboration within the team, and encourage sustainable human resource development. Thus, the implementation of situational leadership is the right strategy in optimizing workforce potential and supporting the achievement of organizational performance more effectively.